Advancing writing proficiency through mobile learning: exploratory factor analysis among Uzbekistan EFL undergraduates - Khamraeva, Dilfuza Shavkatovna; Harwati Hashim,; Khairul Azhar Jamaludin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
It is crucial to comprehend how EFL undergraduates accept mobile learning as it gets more and more included in higher education. Few studies examine the underlying factor structure of mobile learning acceptance in EFL contexts, even though there are numerous models available for evaluating technology adoption. The validity and reliability of the constructs related to Uzbekistan EFL undergraduates’ acceptance of mobile learning are examined in this study. Participants in the study included 732 students from five Uzbekistan public universities. Seven major factors: cultural factors, normative beliefs, motivation to comply, perceived language learning potential, comprehensible input, self-management of learning, and behavioral intention were identified through exploratory factor analysis, which consisted of 26 items. Bartlett’s test was significant (p < 0.001) and the Kaiser-Meyer-Olkin measure of sampling adequacy was 0.897, indicating that the dataset was appropriate for factor analysis. A well-structured factor solution was also indicated by the fact that all of the retained items had factor loadings above the acceptable threshold except one. The findings imply that the identified constructs offer a valid and trustworthy framework for understanding mobile learning acceptance in EFL education for enhancing writing skills.